Mainstreaming Solar Energy into Residential Sectors of Nashik City (Global Journals of Research in Engineering, 2022)
Energy is one amongst the foremost vital inputs for economic growth and human development. The economic progress and urbanization are leading to rapid increase in energy demand in urban areas. With appreciation in income levels, people have started depending more on electrical run appliances for their domestic needs. Growth in industrial and commercial sectors also has an ever increasing demand for power supply. Urban areas are heavily dependent on fossil fuels for powering homes, infrastructure, transport, industry and commerce. Although India has huge proven coal reserve, the calorific value and increasing ash content in Indian coal is a major concern. With the proven statistic the oil and natural gas resource in India will last hardly for 18 and 26 years. Most cities of India are experiencing 15% growth in the peak electricity demand. The government and electricity utilities are finding it difficult to cope with rapid rise in demand, as a result most of cities are facing severe electricity shortages. Long hours of power cuts results in disruption of activities and severely affect economic development of city. With increased dependency on fossil fuels, urban areas have emerged as one of the major sources of Green House Gas (GHG) emissions, with buildings alone contributing to around 40% of total GHG emissions. CO2 emissions are creating serious global warming issues. SOx, NOx and SPM are contributing to local environmental impacts and flattering a challenge for human well being. In this context there is need to develop a framework that will encourage and assist cities in assessing their present energy consumption status, setting clear targets for and preparing action plans for generating energy through renewable energy sources and in conserving energy utilized in conducting urban services. This paper provides a framework to harness solar energy potential to reduce the burden of peak energy demands of urban areas.
Keywords: solar energy; urban areas; energy conservation; environment; grid; sewage